Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.4178/epih.e2023098
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific findings on lifestyle and trajectories of cognitive function from the Korean Longitudinal Study of Aging

Seungju lim,
Eunyoung Yoo,
Ickpyo Hong
et al.

Abstract: OBJECTIVES: Few longitudinal studies have explored age-related differences in the relationship between lifestyle factors and cognitive decline. This study investigated lifestyle factors at baseline that slow the longitudinal rate of cognitive decline in young-old (55-64 years), middle-old (65-74 years), and old-old (75+ years) individuals.METHODS: We conducted an 11-year follow-up that included 6,189 older adults from the Korean Longitudinal Study of Aging, which is a cohort study of community-dwelling older K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous research has demonstrated the association between unhealthy lifestyles and aging. 34 Furthermore, our study identified a significant interaction between smoking and diet in relation to aging. Among smokers in the NHANES cohort, the risk of accelerated aging decreased as the dietary quality improved, with lower ORs observed in smokers compared to non-smokers.…”
Section: Discussionmentioning
confidence: 66%
“…Previous research has demonstrated the association between unhealthy lifestyles and aging. 34 Furthermore, our study identified a significant interaction between smoking and diet in relation to aging. Among smokers in the NHANES cohort, the risk of accelerated aging decreased as the dietary quality improved, with lower ORs observed in smokers compared to non-smokers.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, engagement in social activities is frequently evaluated alongside the engagement in cognitive activities, such as reading, gaming, puzzling ( 36 , 37 ). Typically, item scores are merged into a single composite score ( 38 , 39 ), which overlooks the separate and distinct influence of social activities. Additionally, a high level of heterogeneity is observed across studies in terms of the thematic content of items, response scales utilized, and the recall periods specified ( 28 ).…”
Section: The Concept Of Engagement In Social Activities: Definition A...mentioning
confidence: 99%